2020
DOI: 10.2298/tsci180527024m
|View full text |Cite
|
Sign up to set email alerts
|

Performance investigation and exergy analysis of vapor compression refrigeration system operated using R600a refrigerant and nanoadditive compressor oil

Abstract: Compression of vaporized refrigerant is the essential process of the refrigeration cycle which is performed by using a compressor. The amount of power consumed by a refrigeration system is governed by the work input given to its compressor, which also determines the COP of the system. By reducing the work input given to the compressor, the power consumption of refrigerator is reduced along with the improvement in its COP. Nowadays, nanoparticles have emerged as the new generation additives in various working f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Also reported that 40 g of LPG refrigerant with 0.4 g/L of TiO2 achieved the best energy performance of the refrigerator (Gill et al, 2019). Karthick et al (2020) evaluated the performance of VCRs based on four samples of nano-lubricant: Sample 1 (MO + 0.02 vol% Al2O3 + 0.01 vol% TiO2), sample 2 (MO + 0.01 vol% Al2O3 + 0.005 vol% TiO2), sample 3(MO + 0.05 vol% Al2O3) and sample 4 (MO + 0.02 vol% Al2O3 + 0.02 vol% ZnO). R600a was charged as a refrigerant.…”
Section: Literature Reviewmentioning
confidence: 96%
See 2 more Smart Citations
“…Also reported that 40 g of LPG refrigerant with 0.4 g/L of TiO2 achieved the best energy performance of the refrigerator (Gill et al, 2019). Karthick et al (2020) evaluated the performance of VCRs based on four samples of nano-lubricant: Sample 1 (MO + 0.02 vol% Al2O3 + 0.01 vol% TiO2), sample 2 (MO + 0.01 vol% Al2O3 + 0.005 vol% TiO2), sample 3(MO + 0.05 vol% Al2O3) and sample 4 (MO + 0.02 vol% Al2O3 + 0.02 vol% ZnO). R600a was charged as a refrigerant.…”
Section: Literature Reviewmentioning
confidence: 96%
“…The results reported that decreasing these values with increase of temperatures and kinematic viscosity of 0.4 vol% nanolubricants was 14% higher than pure oil at room temperature (Harichandran et al, 2019). Karthick et al (2020) investigated thermal conductivity of four samples such as, sample1 (MO+ 0.02 vol% Al2O3 + 0.01 vol% TiO2), sample 2 (MO+0.01 vol% Al2O3+ 0.005 vol% TiO2), sample 3 (MO + 0.05 vol% Al2O3) and sample 4 (MO+ 0.02 vol% Al2O3 + 0.02 vol% ZnO). The results showed that MO based on 0.05 vol% of Al2O3 produced a higher increase of thermal conductivity and MO containing 0.01vol% Al2O3 and 0.005 vol% of TiO2 produced the least increase in thermal conductivity.…”
Section: Literature Reviewmentioning
confidence: 96%
See 1 more Smart Citation
“…This is around a 6.9 percent rise. In contrast to the R134a refrigerant, the power consumption was also reduced to 50 % [15]. The addition of Nano Al2O3 to the refrigerant suggests an increase in the cooling system's COP.…”
Section: Introductionmentioning
confidence: 94%
“…Additionally, the power consumed was lower than R134a by approximately 3.20–18.1. Karthick et al 15 studied the effect of nanolubricants on the performance of a refrigeration system based on the following samples: sample 1 (mineral oil + 0.02 vol% Al 2 O 3 + 0.01 vol% TiO 2 ), sample 2 (mineral oil + 0.01 vol% Al 2 O 3 + 0.005 vol% TiO 2 ), sample 3 (mineral oil + 0.05 vol% Al 2 O 3 ), and sample 4 (mineral oil + 0.02 vol% Al 2 O 3 + 0.02 vol% ZnO). R600a was used as a refrigerant.…”
Section: Introductionmentioning
confidence: 99%